Communication and innovation in the performance of weaving and pottery crafts in Gojjam, Ethiopia - Wondifraw Mihret Dessie; Gojjam Ademe Mengistu; Tigist Abera Mulualem (Journal of Innovation and Entrepreneurship, 2022)
Competitive organizations harness information and knowledge sharing undertakings to take risks and break customary routines. This study investigates craftspeople's communication practices and innovation implementation towards improving business performance. Cross-sectional survey research design was employed to describe and see the association of communication and innovation with business performance. Data were collected from a sample of 326 craftspeople through structured questionnaire and field observation. Both descriptive and Structural Equation Modeling (SEM) statistics were mainly used to analyze data. Findings revealed that communication practices vital for craftspeople to be innovative and integrate them with clients were negligible. The communication flaws in turn resulted in stagnant and in-house limited trifling inventiveness in craft industries. Moreover, reflexivity, frequency of communication on creativity, product and market innovation were significantly associated with craftspeople's performance. Hence, it is recommended to arrange training and experience sharing schemes for craftspeople to enhance their communication and innovation skills thereby improve performance.
Keywords: 650; Business performance; Communication; Craft industries; Innovation; Pottery; Strategic communication; Weaving